The high walls of Jerusalem a history of the Balfour Declaration and the birth of the British mandate for Palestine - Sanders, Ronald (Holt, Rinehart and Winston, 1984)
A study of the Balfour Declaration examines its impact on the creation of the British mandate for Palestine.
Keywords: Balfour-Deklaration -- 1917 November 02; Balfourdeclaratie; Mandaat; Außenpolitik; Balfour Declaration; Zionism -- Great Britain; Vorgeschichte; Großbritannien; Naher Osten; Great Britain -- Foreign relations -- Middle East; Middle East -- Foreign relations -- Great Britain